If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=-6y+3(y-6)
We move all terms to the left:
12-(-6y+3(y-6))=0
We calculate terms in parentheses: -(-6y+3(y-6)), so:We get rid of parentheses
-6y+3(y-6)
We multiply parentheses
-6y+3y-18
We add all the numbers together, and all the variables
-3y-18
Back to the equation:
-(-3y-18)
3y+18+12=0
We add all the numbers together, and all the variables
3y+30=0
We move all terms containing y to the left, all other terms to the right
3y=-30
y=-30/3
y=-10
| -1/3x+4=1/2x-1/6 | | 63=-7p | | 5x-16=2x+21 | | 13.59140914^(x-4)=19 | | 2=m+9 | | 3a+(25+a)=225 | | -9+7n=12 | | 3z+2=(−5z)+6 | | b=0.75(21-b) | | 9x-(5x-15)=50 | | 6(r-4)=29r-8)=+3r | | -16x+-48=-16x+-48 | | X=(1/3)x+6 | | 5a=28+7 | | 12+18=4+5n | | 7x×7=7 | | 3w-48=-3w=4 | | 3x-7=20+x | | 216=-y+106 | | 218-u=166 | | 20=16+2a | | 2x-4(2-x)=2(15x-3 | | -5=-2+m/5 | | x/4+16=37 | | 5b-16=14 | | 3k−-10=19 | | 6(x+2)–4=-10 | | x/6=4.3 | | -6|-6m|=-72 | | 1x+12-8x=8.5 | | 3(x+9)^2=63 | | 2x-5=-3x-40 |